(untitled) ("Journal "U". Economy. Management. Finance.", 2019)
This article examines the features for the countries to transition to a circular type of economy or to the «future economy». Sustainable development of society is possible only with a simultaneous positive impact on the social, environmental and economic spheres. The author shows the specific differences in the process of consumption of goods of different types of economic development. Based on the analysis of the transition of the country’s economy from linear to cyclical type, the specifics of the transformation of business processes of enterprises and the development of strategies for changing the consumption of the product are determined.